APPROACHES IN DESIGNING EFFECTIVE CLASSROOM MANAGEMENT SYSTEM: A COMPARATIVE STUDY - Wahdah, Wahdah; Prayuda, Meikardo Samuel; Juliana, Juliana; Ginting, Fiber Yun Almanda; Gultom, Candra Ronitua (Universitas Islam Sumatera Utara (UISU), 2023)
The research is intended to determine the best approach to managing classrooms. There are discussions regarding the comparison of approaches that have proven effective in designing effective classroom management. Student achievement could not be separated from a successful classroom management system. The learning environment in the class is based on how well teachers build effective classroom management systems. It leads to the students’ well-being in the learning process. In order to achieve a successful classroom management system, teachers tend to apply different approaches. There are some studies that deal with the application of these approaches in the process of creating such an effective classroom management system. Two of them are the behavior modification approach and the analytical pluralistic approach. This research is completed by using quantitative approach. The findings lead to the conclusion that certain approaches have proven better through this experimental research. At the end of the research, readers might benefit by taking the result of this research as a reference in their daily teaching.